Comparison and Extension of Approximate 4-2 Compressors for Low-Power Approximate Multipliers - Strollo, Antonio Giuseppe Maria; Napoli, Ettore; De Caro, Davide; Petra, Nicola; Meo, Gennaro Di (IEEE transactions on circuits and systems. I, Regular papers, 2020)
Approximate multipliers attract a large interest in the scientific literature that proposes several circuits built with approximate 4-2 compressors. Due to the large number of proposed solutions, the designer who wishes to use an approximate 4-2 compressor is faced with the problem of selecting the right topology. In this paper, we present a comprehensive survey and comparison of approximate 4-2 compressors previously proposed in literature. We present also a novel approximate compressor, so that a total of twelve different approximate 4-2 compressors are analyzed. The investigated circuits are employed to design 8× 8 and 16× 16 multipliers, implemented in 28nm CMOS technology. For each operand size we analyze two multiplier configurations, with different levels of approximations, both signed and unsigned. Our study highlights that there is no unique winning approximate compressor topology since the best solution depends on the required precision, on the signedness of the multiplier and on the considered error metric.